Formation Kinetics and Morphology Characteristics of Natural Gas Hydrates in Sandstone Fractures - Chaozheng Ma; Xiaoxu Hu; Hongxiang Si; Jiyao Wang; Juntao Pan; Tingting Luo; Tao Han; Aowang Wang (Applied Sciences, 2025)
Fractures in marine sediments are critical zones for hydrate formation. The kinetics and morphological characteristics of hydrates within sandstone fractures are comprehensively investigated in this study by employing a high-pressure visualization reaction vessel to examine their formation, dissociation, and reformation processes. The results are presented below: (1) In 3 mm Type I fractures, the induction time is longer than that observed in the other two fracture widths. Hydrates predominantly form on the fracture walls and gradually expand toward both sides of the fracture. (2) Gas enters the fracture from multiple directions, causing the hydrate in Type X fractures to expand toward the center from all sides, which shortens the induction time and increases the quantity of hydrate formation. (3) An increase in fracture roughness promotes nucleation of the hydrate at surface protrusions but inhibits the total quantity of hydrate formation. (4) Hydrate dissociation typically propagates from the fracture wall into the interior, exhibiting a wavy surface morphology. Gas production is influenced by the fracture width, with the highest gas production observed in a 3 mm fracture. (5) Due to the memory effect, the hydrate induction time for reformation is significantly shorter, though the quantity of hydrate formed is lower than that of the first formation. This study aims to provide micro-level insights into the distribution of hydrates in sandstone fractures, thereby facilitating more efficient and safe extraction of hydrates from fractures.